EFFECT OF ROLE CONFLICT AND ROLE OVERLOAD TO BURNOUT AND ITS IMPACT ON CYBERLOAFING (STUDY ON PT PLN (PERSERO) PUSAT MANAJEMEN KONSTRUKSI) - Hardiani, Wenefrida Ardhian ayu; Rahardja, Eddy; Yuniawan, Ahyar (JURNAL BISNIS STRATEGI, 2017)
Cyberloafing is one of the employee's counterproductive behavior by using mobile phone and office internet facility for personal use during working hours. Cyberloafing behavior is caused one of them by the psychological condition of employees, namely burnout. The cause of this burnout is due to role conflict and role overload. If the behavior of cyberloafing continues to be done will hamper the productivity of employees and eventually will have a negative impact on the company. The problem in this research is how to decrease cyberloafing by seeing role conflict, role overload, and burnout. The sample of this study amounted to 150 respondents. Sample determination was done by census technique. Respondents in this research are employees of PT PLN (Persero) Pusat Manajemen Konstruksi Semarang. The analysis tool used is Structural Equation Modeling (SEM) in AMOS 22 program.Based on five hypotheses tested, there are four accepted hypotheses. Role conflict has a significant effect on cyberloafing, role overload has no effect on cyberloafing, role conflict and burnout has a significant effect on burnout, and burnout has a significant effect on cyberloafing. In an effort to decrease the level of cyberloafing, good human resource management is required. Purpose of Human resource management is to avoid role conflict, role overload, and burnout affecting cyberloafing.